The Role Of Social Responsibility Of Iraqi Sports Clubs In Improving The Sustainable Development Of Society From The Perspective Of Some Employees In The Ministry Of Youth And Sports And Sports Clubs - Jassim Ali Mohammed (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The study aimed to clarify the role of social responsibility as an effective tool in measuring the role of sports clubs and their contribution to achieving sustainable development in Iraq, through building two scientific scales that measure the level of social responsibility and the fields of sustainable development within sports institutions. The two research scales were built and applied to a sample of employees from the Ministry of Youth and Sports and some of its affiliated clubs, where the research sample consisted of (170) individuals distributed as (90) individuals for scale construction, (70) individuals for applying the two scales, and (10) employees from sports clubs for the exploratory sample, representing (34%) of (500) individuals comprising the original population of the study from employees at the Ministry of Youth and Sports and some affiliated sports clubs in Baghdad and the southern governorates (Maysan, Basra, Dhi Qar). The researcher used the descriptive method with a correlational approach as it suited the nature of the study problem and its objectives. After constructing the two scales and applying them to the study sample, and through what the research results showed after statistical treatments, analysis, and discussion, the researcher inferred the existence of a significant correlation between the level of social responsibility of sports clubs and their role in achieving sustainable development in Iraq. The levels of each of the dimensions (social, ethical, educational, and economic) appeared high, whereas the environmental performance dimension was relatively low. Through the study results, the researcher reached several recommendations, the most important of which are: the necessity to enhance the environmental aspect within the social responsibility plans of sports clubs in Iraq, and to adopt the results of the social responsibility and sustainable development scales as a reference when evaluating the performance of sports clubs and clarifying their social responsibility in developing and achieving community development in Iraq.